Development of validated liquid chromatographic method for estimation of levocetirizine from pharmaceutical dosage forms - Chaitanya Prasad MK, Vidyasagar G, Sambasiva Rao KRS, Madhusudhanareddy Induri, Ramanjeneyulu S (Journal of Applied Pharmaceutical Science)
A simple and rapid high-performance liquid chromatographic (HPLC) method for the determination levocetirizine has been developed. The chromatographic system consisted of a Water 2695 binary gradient pump, Water 2487 dual wavelength absorbance detector, and Empower 2 software. Separation was achieved on the XTerra symmetry C18 column at room temperature. The sample was introduced through an injector valve with a 20 μL sample loop. The results obtained showed a good agreement with the declared content. Recovery values of levocetirizine in tablets were from 99.57-100.48 %. The proposed method is rapid, accurate and selective; it may be usedfor the quantitative analysis of levocetirizine from raw materials, in bulk drugs and other dosage formulations.
Keywords: Levocetirizine, Tablets, Reverse phase, HPLC and Quality control.